Book Reviews (Journal of Finance, 2002)
ABSTRACT Brennan, Michael J. Financial Markets and Corporate Finance: Selected Papers of Michael J. Brennan Hallock, Kevin F. and Murphy, Kevin J. The Economics of Executive Compensation Epps, T. W. Pricing Derivative Securities